Development of an Integrated Web-Based Academic and Administrative Information System with E-Learning and Student Interest Recommendation - Ahmad Hasan Faqih Aulia; Muhammad Raihan Zaldiputra; Ardien Ferdinand Putra Setiawan; Ridho Putra Pratama; Sofiyanti Indriasari; Medhanita Dewi Renanti (J-INTECH ( Journal of Information and Technology), 2026)
The advancement of information technology in the education sector has driven the need for digital transformation in managing academic and administrative processes, including in Early Childhood Education (ECE) institutions. However, many ECE institutions, such as BKB PAUD Bougenville, still rely on manual and fragmented systems for managing student data, attendance, assessments, and learning materials, which often leads to inefficiencies, data inconsistencies, and delays in information processing. This study aims to develop an integrated web-based academic and administrative information system that incorporates e-learning features and student interest recommendations to support more effective and structured educational management. The system is developed using the Agile methodology, which emphasizes iterative development, continuous user involvement, and adaptive improvements based on user feedback to ensure alignment with real operational needs. The proposed system integrates several core modules, including student data management, attendance recording, e-learning through digital materials (e-books), assessment processing, and a data-driven student interest recommendation feature. The implementation results indicate that the system is able to improve data management efficiency, facilitate real-time access to academic and administrative information, and reduce the risk of data inconsistencies. In addition, the interest recommendation feature provides practical benefits by assisting teachers in identifying student potential and supporting more informed decision-making processes. Therefore, this research contributes to the development of an integrated, user-friendly, and adaptive digital platform that enhances the quality of academic and administrative services in the PAUD environment.